Inventarisasi Tanaman Obat di Sumber Sehat Multifarm, Ciampea, Bogor : Inventory of Medicinal Plants at Sumber Sehat Multifarm, Ciampea, Bogor - Asardi, Istiqoma; Chikmawati, Tatik; Ratna Djuita, Nina (Jurnal Sumberdaya Hayati, 2025)
The use of medicinal plants to treat disease is still used in many areas. This research aimed to provide information about medicinal plants in Sumber Sehat Multifarm. Data such as local name, scientific name, habitus, part of the plants that are used, benefits, how to use, and also plant processing were collected through a semi-structured interview method. Data analysis was done through a quantitative method which calculated calculating the percentage of parts of the plants that were used and the habitus of the plants that were found. Qualitative analysis of data was done descriptively. The result showed that Sumber Sehat Multifarm uses 177 species belonging to 64 families as medicinal plants. Most plant species have herbaceous habitus. Part of the plants that are used mostly are the leaves. Most plant species of plant can treat more than one kind of disease. The benefits of the plant can be grouped into two categories: plants used to cure internal organ disease and plants used to treat external organ disease. Most plant species can be consumed by brewing or freshly eaten.